2008
DOI: 10.5194/angeo-26-13-2008
|View full text |Cite
|
Sign up to set email alerts
|

Parameterisation of the chemical effect of sprites in the middle atmosphere

Abstract: Abstract. Transient luminous events, such as red sprites, occur in the middle atmosphere in the electric field above thunderstorms. We here address the question whether these processes may be a significant source of odd nitrogen and affect ozone or other important trace species. A well-established coupled ion-neutral chemical model has been extended for this purpose and applied together with estimated rates of ionisation, excitation and dissociation based on spectroscopic ratios from ISUAL on FORMOSAT-2. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 56 publications
6
87
1
Order By: Relevance
“…The 20% magnitude led to statistically significant changes which were extrapolated down to the scenarios of Enell et al (2008) adopting the linear dependence of the radiatively driven response found in the uniform experiments. The local response of the two models to this regional perturbation was fairly similar, leading to a maximum temperature change of 0.3 K at 60-70 km over extraordinary active TLE-producing thunderstorms and of the order of at most 0.015 K at 60-70 km height in typical TLE scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The 20% magnitude led to statistically significant changes which were extrapolated down to the scenarios of Enell et al (2008) adopting the linear dependence of the radiatively driven response found in the uniform experiments. The local response of the two models to this regional perturbation was fairly similar, leading to a maximum temperature change of 0.3 K at 60-70 km over extraordinary active TLE-producing thunderstorms and of the order of at most 0.015 K at 60-70 km height in typical TLE scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…A linear scaling of the peak temperature change of 3 K obtained in this 20% ozone reduction experiment to account for the maximum (insignificant) 0.1% ozone change of the typical TLE scenario by Enell et al (2008), leads to an impact of TLEs on atmospheric temperature at 60-70 km of at most an average 0.015 K. On the other hand, adopting Enell et al (2008) maximum case scenario of possibly a local few percent change above extraordinary active sprite producing thunderstorms, the extrapolated temperature change would be at most a localised 0.3 K over a 200 km×50 km region at sunrise. Likely, any such a radiative change would last at most for a few hours before photochemistry and mixing vanished the ozone change, thus with a negligible impact on the atmospheric temperature.…”
Section: The Regional Mid-latitude Upper-stratosphere Perturbationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that sprites can have an impact on upper stratospheric and mesospheric ozone chemistry, which is triggered by a cluster of streamers having the above characteristics (Stenbaek-Nielsen et al, 2000;Sentman and São 3920 Y. Hiraki et al: Chemistry of sprite discharges Sabbas, 2002;Hiraki et al, 2004;Enell et al, 2005Enell et al, , 2008Arnone et al, 2008). Here, we make a rough estimation as to how large an impact is actually expected from the generation of ions and atoms (e.g.…”
Section: Introductionmentioning
confidence: 98%